Pengaruh Pemanfaatan Kelas Digital terhadap Prestasi Belajar Siswa di MA Unggulan KH. Abd. Wahab Hasbulloh Tambakberas Jombang - Yasaroh, Ririn Maskurin Ardila; Zulfah, Machnunah Ani; Hidayatulloh, Muhammad Kris Yuan (Universitas KH. A. Wahab Hasbullah, 2022)
This study uses a type of field research. The research sample was 30 respondents. The research data that has been collected is then analyzed using statistical analysis techniques. Testing the research hypothesis using Product Moment correlation analysis. This research shows that: (1) The use of digital classes in MA Unggulan K.H.Abd.Wahab Hasbullloh Tambakberas Jombang is in the